Plate Osteosynthesis of Bilateral Ilial Body Fracture using String of Pearls Plate in a Non-Descript Dog - Rajendran, Thavasi; Shafiuzama, Mohamed; Haridoss, Pushkin Raj; Ramamurthy, Sathyamoorthy Ommini (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
This case report describes the clinical signs, diagnostic findings, and surgical management of bilateral ilial body fracture in a dog, with fixation achieved using a String of Pearls plate for effective stabilization and anatomical reconstruction.